A perspective: Regeneration of soft and hard tissues in the oral cavity, from research to clinical practice - Puterman, Israel; Fien, Matthew J.; Mesquida, Juan; Ginebreda, Ignacio; Bauza, Guillermo; Somerman, Martha (Frontiers in Dental Medicine, 2023)
Regenerative medicine has gained much attention and has been a hot topic since its birth in all medical areas and dentistry is no exception. However, innovations and developments in basic research are sometimes disconnected from everyday clinical practice. This existing gap between basic research and clinical practice can only be addressed with improved communication between clinicians, academicians, industry, and researchers to facilitate the advance of evidence-based therapies and procedures and to direct research into areas of clinical need. In this perspective, six participants with strong clinical and research interests debated five previously conceived questions. These questions covered current methods and procedures for soft and hard tissue regeneration of the oral cavity with predictable outcomes, limitations of the respective protocols, and needs for future development regarding regenerative materials and technologies.